Warm dense aluminum plasma generated by the free-electron-laser FLASH - Zastrau, U; Vinko, S; Wark, J; Toleikis, S; Tschentscher, T; Glenzer, S; Lee, R; Nelson, A; Dzelzainis, T; Riley, D; Nagler, B; Galtier, E; et al. (2012)
We report on experiments aimed at the generation and characterization of solid density plasmas at the free-electron laser FLASH in Hamburg. Aluminum samples were irradiated with XUV pulses at 13.5 nm wavelength (92 eV photon energy). The pulses with duration of a few tens of femtoseconds and pulse energy up to 100 μJ are focused to intensities ranging from 10 13 to 10 17 W/cm 2. We investigate the absorption and temporal evolution of the sample under irradiation by use of XUV spectroscopy. We discuss the origin of saturable absorption, radiative decay, bremsstrahlung and ionic line emission. Our experimental results are in good agreement with hydrodynamic simulations. © 2012 American Institute of Physics.